Economics of Private Tutoring: In Search for Its Causes and Effective Cures - Yoonha Yoo (Korea Development Institute (KDI), 2002)
This book tries to uncover the economic forces at work under the phenomenon known as private tutoring, a social headache the Korean society has long grappled to cope with. Finding the real economic causes behind private tutoring would facilitate formulating effective cures for the disease, if it can be called a disease at all. Broadly speaking, students take private tutoring for two distinct purposes: for successfully advancing to the next stage of the hierarchical ladder of education, and for entering a better quality school. This book explores the economic incentives working at these two fronts.
Keywords: 330